Changes in chronic disease management among community health centers (CHCs) in China: Has health reform improved CHC ability?. (22nd June 2017) - Wang, Zhaoxin; Shi, Jianwei; Wu, Zhigui; Xie, Huiling; Yu, Yifan; Li, Ping; Liu, Rui; Jing, Limei
Summary: Since the 1980s, China has been criticized for its mode of chronic disease management (CDM) that passively provides treatment in secondary and tertiary hospitals but lacks active prevention in community health centers (CHCs). Since there are few systematic evaluations of the CHCs' methods for CDM, this study aimed to analyze their abilities. On the macroperspective, we searched the literature in China's largest and most authoritative databases and the official websites of health departments. Literature was used to analyze the government's efforts in improving CHCs' abilities to perform CDM. At the microlevel, we examined the CHCs' longitudinal data after the New Health Reform in 2009, including financial investment, facilities, professional capacities, and the conducted CDM activities. A policy analysis showed that there was an increasing tendency towards government efforts in developing CDM, and the peak appeared in 2009. By evaluating the reform at CHCs, we found that there was an obvious increase in fiscal and public health subsidies, large‐scale equipment, general practitioners, and public health physicians. The benefited vulnerable population in this area also rose significantly. However, rural centers were inferior in their CDM abilities compared with urban ones, and the referral system is still not effective in China. This study showed that CHCs are increasingly valued in managing chronic diseases, especially after the New Health Reform in 2009. However, we still need to improve collaborative management for chronic diseases in the community and strengthen the abilities of CHCs, especially in rural areas.